Linguistic Variation in the Direct Transmission of Modern Texts: from Classical Stemmatics to Digital Humanities (Islas, 2025)
Introduction: This article aims to provide a theoretical review of linguistic variation in the direct transmission of modern texts, based on the main principles and procedures of textual criticism. The study takes as its starting point the postulates of classical stemmatics and traces their evolution to the current trends in Digital Humanities.Methods: The study is descriptive in nature, relying on a critical documentary review of the main available sources through bibliographic and documentary analysis techniques.Results: The findings reveal a lack of consensus among the main theoretical approaches addressing linguistic variation in the direct transmission of modern texts, as well as an overlap of concepts that refer differently to the same phenomenon. Furthermore, there is an evident insufficiency of research conducted outside the conventional axioms of classical textual criticism, despite the diversity of its theoretical perspectives.Conclusions: The principles of textual criticism require, first and foremost, a paradigm shift that embraces general procedures for studying modern textual traditions. For the proper development of this discipline in the current context, an interdisciplinary approach is necessary to enable a more comprehensive and efficient analysis of linguistic variation.
Keywords: direct textual transmission of modern texts; textual criticism; direct textual tradition; linguistic variation in modern texts; Digital Humanities